Representações de diferentes atores sociais sobre o trabalho: ergonomia e saúde - um estudo de caso. - Bernardino, Mônica Thais Simões Matsukura (2006)
This research is based upon theoretical concepts from Work Ergonomics Analysis, Action-Research and Occupational Health fields. The study approaches the capacitation experience of an Ergonomics Committee at the Brazilian Post-office Company (Empresa Brasileira de Correios e Telegrafos ECT). The objective has been to conceptually comprehend and discuss the possibilities of considering the viewpoint about the work from workers, different hierarchic levels members, and the Ergonomics Comitee in order to elaborate an ergonomics intervention proposal and support the capacitation process. In order to accomplish these goals, different social actors involved with the work developed at the Local Distribution Centers (Centros de Distribuição Domiciliar CDD) such as mailmen, immediate chefs, regional and state managers and central administrators as well as the Ergonomics Committee members have been interviewed and their statements have been analyzed. As result from this analysis it can be inferred that a) the perception about the work reality has a direct relationship with the institutional insertion level of different social actor groups; b) taking in consideration the representation that each social actor group has about the real work performed allows for achieving a broader comprehension on key factors related to work overload and work health harm; c) the Ergonomics Committee s perception on issues related to ergonomics, work and health and the consequent position it has taken, has improved along capacitation process.